Media, body and market: formative (im)possibilities in the face of the symbolic power - Sérgio Dorenski Dantas Ribeiro; Cristiano Mezzaroba (Universidade Federal de Santa Catarina, 2019)
In this study we focus on the media discourse and its strategies in the face of an increasingly intense market regarding the body archetypes that have gained prominence in modernity. The essay outlines a critical reflection about the influence of the media on the worship of the body, whether by the image or by the explicit and implicit discourse of what has been characterized as the 'perfect body'' nowadays, which we can infer as the way through which the symbolic power acts on people's subjectivity and generates a demand from the subjects to the personalized, exclusive and specific products, offered as 'miraculous' by the media market. In a society increasingly shaped by media discourses, we understand that the possibility of confrontation lies partly in the human formation that takes place in school mediation (its set of knowledge). When we consider the field of teacher training, we believe that an approach that allows the critical reading of these mechanisms is increasingly necessary, highlighting the relevance of media-education to a society in search for the clarification that needs to be confronted with a certain discursive domination and mediamarket. Our objective was to analyze, with the discussion about the cultural industry and the symbolic power, some mechanisms that make these representations about the body in the contemporaneity be demarcated in an intense way with market goals. In addition, we present some examples of research that have already been conducted, in which we identify possible formative and methodological strategies in which the principle of autonomy and enlightenment can occur, implying possibilities for school mediation, especially for those who deal with human formation.